Load and crack detection using smart materials - Zhang, Yuwen (2016)
It is vital to monitor the condition of an engineering structure during its lifespan from the construction stage to the termination of service. Recent years have seen a rapid development of smart materials in structural health monitoring (SHM). The piezoelectric transducer, commonly made of Lead Zirconate Titanate (PZT), is one of the emerging smart materials in SHM applications. It can be used in various SHM approaches such as guided wave and acoustic emission, but electro-mechanical impedance (EMI) is a fast developing and promising technique in SHM. EMI has proven its ability to detect loads, cracks, and vibrations in both laboratory and practice, especially during the construction of a Mass Rapid Transit station at Telok Blangah, Singapore. This Final Year Project (FYP) investigated the PZT transducer for (a) its sensing region on a cable structure, (b) plastic zone detection, and (c) combined load and crack detection on an aluminium beam. This EMI based SHM technique works on the principle of obtaining signals known as admittance signature. If this signature varies during monitoring, there is a possibility of changes in the integrity of the structure. In this study, qualitative analysis of the admittance signature and quantitative analysis using statistical root mean square (RMSD) index were performed for signal processing. The sensing region of the PZT transducer on a cable structure was found by altering the distance between PZT transducers and the applied load. Plastic zone detection was achieved on a 1D laboratory specimen through axial tensile loading test. PZT based EMI was for the first time verified for its capability to detect combined load and crack with prior knowledge on the scale of loads and cracks. Besides, recent technology using the metamaterial, an artificially engineered material, has shown its potential applications in SHM. This FYP presents some pioneering research on the feasibility of the metamaterial in SHM applications. The characteristics of wave transmission, one of the fundamental properties of the metamaterial, were investigated for structures made of various materials. Experiment results testified that the stable transmission signals are applicable for SHM applications. More experiments are recommended to be conducted to expand the understanding of the sensing capability of both PZT based EMI and the metamaterial.